Comprehensive Model Of The Provision Of The Prohibition Of The Wife’s Employment In Iranian And Egyptian Laws Based On The Imamiyyah Jurisprudence - SHAFIEI FINI, H.; AKHTARSHENAS, F. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT In recent years, due to the increasing number of court cases, the question of women's right to employment has become a significant challenge in the legal system. Challenges such as “the superior principle” regarding women's right to employment, employment criteria, and the prohibition of employment are discussed in this article. Various approaches of different authors and the respective judicial processes have been elaborated in a rational framework and, in an attempt to offer a framework for responding to employment disputes concerning the jurisprudential history and the jurisprudents’’ points of view, each has been thoroughly investigated. RESUMEN En los últimos años, debido al creciente número de casos judiciales, la cuestión del derecho de las mujeres al empleo se ha convertido en un desafío importante en el sistema legal. En este artículo se discuten desafíos como "el principio superior" con respecto al derecho de las mujeres al empleo, los criterios de empleo y la prohibición del empleo. Se han elaborado varios enfoques de diferentes autores y los procesos judiciales respectivos en un marco racional y, en un intento de ofrecer un marco para responder a disputas laborales relacionadas con la historia jurisprudencial y los puntos de vista de los jurisprudenciales, cada uno ha sido investigado a fondo.